China as a 'new frontier': Neo-liberal aspirations, imaginaries and (dis-) enchantments of Swiss migrant professionals in mainland China. Issue 1 (1st March 2019) - Camenisch, Aldina
Mainland China has emerged as a migration destination for foreign professionals in the post-Mao era. This ethnographic article investigates the aspirations of one group among them – self-initiated Swiss migrant professionals – and the imaginative geographies of China that they develop and renegotiate throughout their journeys. The analysis reveals their aspirations and imaginaries signifying a quest to push limits for the sake of neo-liberal self-development. Swiss professionals encounter a China in transformation as a 'country of extremes' and approach it as a 'new frontier'. Rich in challenges and opportunities, it both enables and limits interviewees' projects for self-realization, further fuelling the strong sense of transience that permeates their migration trajectories.